New and Speculative Organisational Aesthetics - Dzidowski, Adam (Organizational Aesthetics, 2015)
The paper attempts to raise the question whether human perception is still central to organisational aesthetics, especially if we start to give a stakeholder position to artificial systems and when organisational designs and processes have ceased to rely only on human agency. Algorithmically driven, autonomous agents like high-frequency trading (HFT), already exist and are acting within the timeframes (milliseconds) and space (global market) that are unreachable for human perception. All that calls for serious consideration whether emerging philosophical trends, such as Speculative Realism, Object-Oriented Ontology, New and Speculative Aesthetics have their impact on organisational perception and design.